PERANCANGAN VIDEO PROMOSI OBJEK WISATA PEMANDIAN ALAM AIA BALIANG - Hardian Afrianvica Novasy,; syafwandi syafwandi; M.nasrul kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
This natural bathing attraction is located on the Padang-Solok causeway precisely at kilometer 14, if from Padang to Solok the location is right on a bend before the Lubuk Paraku bath to Sitinjau Lauik. The atmosphere in Aia Baliang is very natural, the water flowing cold and fresh, plus quite shady trees and a waterfall with a height of about 6 meters adds to the natural impression on this one tourist attraction.The creative purpose of Aia Baliang natural bathing tourism video to be achieved is to design an information media that aims to convey information to the target audience completely, communicatively, attractively and reflect the image of professionalism as expected. The approach used rationally but still packaged attractively, so that the information to be conveyed is achieved effectively.The main media used in designing the promotional video of Aia Baliang natural bathing attraction is Video. In addition to the main media, this promotional video is complemented by supporting media such as X-Banners, t-shirts, posters, hats, drinking bottles, pamphlets and stickers which aim to strengthen the application of the main media.Keywords: Design of Promotion Videos for Nature Baths Aia Baliang, Media